Persepsi Pengguna Terhadap Keberadaan Taman Sampangan Sebagai Kebutuhan Rekreasi - Christine Margaretha Batubara; Diah Intan Kusuma Dewi (Ruang, 2018)
Taman Sampangan apply the concept of conformity of functions of RTH as a recreation area where viewed the existing condition of a crowded park visited by the surrounding community. Visitors are doing recreational activities in Taman Sampangan, such as sports, picnics, children's games. However, hard material and soft material elements do not support visitor activity in Taman Sampangan where jogging tracks are used as parking spaces,  colloseum and gazebo is not shady, broken children's playground equipment, lack of cleanliness due to difficult-to-reach garbage position, lack of lighting due to damage garden lights and spotlights as well as a lack of interest treatments in the park. Thus, it is necessary to do research with the formulation of the question: "Does the existence of Taman Sampangan meet the needs of recreation for the surrounding community based on user perception?". This research uses quantitative approach with frequency distribution analysis. Determination of respondents used Accidential Sampling Method with Guttman Scale measurement. The result of this research is Taman Sampangan fulfill the recreation needs for the surrounding community because there are hard material and soft material. Visitors also perform recreational activities in each landscape element. However, there needs to be improved landscape elements, such as adding vegetation in the gym area, sculpture, children's games, garden entrances, gazebo, and colloseum. In addition, it is necessary to add the absorption hole, laying the trash can could easily be reached and the user realizes the importance of maintaining cleanliness in the park.